Assessment of techno-economic feasibility of centralised seasonal thermal energy storage for decarbonising the Swiss residential heating sector. (December 2020) - Narula, Kapil; De Oliveira Filho, Fleury; Chambers, Jonathan; Romano, Elliot; Hollmuller, Pierre; Patel, Martin Kumar
Abstract: A major part of heat in Swiss residential buildings is supplied by fossil fuel boilers, leading to large CO 2 emissions. Heat supply can be decarbonised by replacing boilers with renewable energy sources (RES) such as solar thermal, but the mismatch between heat supply and heat demand needs to be overcome. Seasonal thermal energy storage (STES) can be used to store heat from solar collector (SC) thereby reducing the usage of boilers. A centralised heat pump (HP) is also an attractive alternative for heating. This paper assesses the techno-economic feasibility of different heating systems for decarbonising the Swiss residential heating sector. It uses the simulation method for assessing hourly energy flows in 500 and 1, 000 multifamily households connected by a district heating (DH) system. Four different configurations of DH system are assessed by simulating hourly energy flows. The required capacity of equipment, cost of different systems, and the cost of decarbonisation of heat are calculated. Levelised cost of heat, CO 2 emissions and share of RES are compared. Peak electricity load due to use of HP and the impact of using different emission factors for electricity is examined. Results show that the heating system with a centralised HP has the least cost of decarbonisation but it adds a high peak load on the electricity grid infrastructure. A heating system with a SC, a STES, HP and a boiler emerges as a cost competitive option for decarbonising heating for 1, 000 dwellings. Highlights: Simulates hourly energy flows in four types of centralised heating systems. Examines techno-economic feasibility of seasonal thermal energy storage (STES). Calculates levelised cost of heat, CO2 emissions and share of renewable energy. Evaluates impact of different CO2 emission factors and cost of decarbonisation. Heating systems with STES are cost competitive with centralised heat pumps.